Konsep dan tantangan dalam implementasi talent management di perusahaan multinasional: Studi kasus PT Unilever Indonesia Tbk - Ahmad Saomin Ali; Aji Hermawan; Yudha Heryawan Asnawi (Universitas Airlangga, 2019)
The purpose of this study is to analyze the understanding responden of Talent Management (TM), concepts, practices and challenges in implementation of TM. Respondents consists of stakeholder (Professional HR, Senior executives, Line Managers) and TM participants. Qualitative approach is adopted in the study with case study at PT Unilever Indonesia Tbk as a multinational company (MNC). Findings in this study indicate that TM implementation will depend on the culture, type of company, and individual of the company. Understanding of the TM concept has different at each level. TM practices at PT Unilever Indonesia Tbk use the inclusive people approach. The TM program is good enough and synergizes with long-term business strategies; however, still has a lot of improvement, and practice of TM more on 70% experience or on the job assignment, 20% coaching and mentoring, and 10% formal development.